Design and Optimization of a Thermal Management System for High-Performance Electric Vehicle Batteries Using Phase Change Materials (The Science Post, 2025)
Effective thermal management is critical for ensuring the safety, performance, and longevity of high-performanceelectric vehicle (EV) batteries. This study presents the design, simulation, optimization, and experimental validation ofa phase change material (PCM)-based thermal management system (TMS) for lithium-ion battery modules. VariousPCM candidates, including composite materials enhanced with thermally conductive additives, are evaluated toimprove heat dissipation and mitigate localized hotspots. A three-dimensional thermal model of the battery pack isdeveloped using computational tools, incorporating heat generation, conduction, convection, and phase changephenomena. Multi-objective optimization is applied to determine optimal PCM thickness, melting temperature, andthermal conductivity to achieve uniform temperature distribution and minimize thermal stress. A small-scale prototypeof the optimized system is fabricated and tested under controlled charge-discharge cycles. Experimental results validatethe simulation findings, demonstrating that the PCM-based TMS effectively reduces peak temperatures, improvesthermal uniformity, and enhances overall battery performance. The proposed methodology provides a practicalapproach for integrating advanced thermal management solutions in EV battery systems.